Characterization of Immune Cell Infiltration in the Placentome of Water Buffaloes (Bubalus bubalis) Infected with Neospora caninum During Pregnancy - Canton, German Jose (2014)
Neospora caninum infection in cattle stimulates host immune responses, which may be responsible for placental damage leading to abortion. Susceptibility of water buffaloes (Bubalus bubalis) to neosporosis is not well understood, although vertical transmission and fetal death have been documented. The aim of this study was to characterize the immune response in the placentome of water buffalo following experimental infection in early gestation with the Nc-1 strain of N. caninum. Placentomes were examined by immunohistochemistry using antibodies specific for T-cell subsets, natural killer cells and CD79αcy cells. Placental inflammation was characterized by the infiltration of CD3+ and CD4+ T cells and T cells expressing the γδ T-cell receptor. The distribution of these cellular subsets in buffalo placentomes was similar to that previously described in cattle infected with N. caninum in early gestation, but the lesions were milder, which may explain the lower number of abortions observed in this species after infection.